Risk Management & Priority Setting - Damani, Nizam (International Journal of Infection Control, 2009)
Key points• It is the responsibility of the Infection Control Team to identify infection control practices which are unsafe and hazardous.• Unsafe practices must be assessed for their likely severity and frequency.• Priority must be given to hazardous practices that have high adverse effects, occur more frequently and have low cost to prevent.• Effectiveness of these measures should be monitored by regular audit and/or surveillance and the information must be fed back to front-line clinical staff and relevant managers.